Sex inequities in the performance of the GRACE 2.0 score in non-ST-segment elevation acute coronary syndromes: a multinational observational study in contemporary cohorts from four European countries. (3rd October 2022) - Wenzl, F; Kraler, S; Weston, C; Ambler, G; Raeber, L; Muller, O; Paneni, F; Camici, G G; Puhan, M A; Roffi, M; Rickli, H; De Belder, M; et al.
Abstract: Background: The Global Registry of Acute Coronary Events (GRACE) score was developed and validated in predominantly male patient populations. Growing evidence indicates distinct pathophysiologic and clinical characteristics of non-ST-segment elevation acute coronary syndromes (NSTE-ACS) in women and men. Purpose: We aimed to assess sex differences in the performance of the GRACE score in NSTE-ACS in contemporary populations. Methods: We calculated GRACE 2.0 risk estimates for patients with NSTE-ACS in contemporary nation-wide ACS cohorts from England, Wales, and Northern Ireland (MINAP, 2005–2017, n=400, 054) and from Switzerland (AMIS Plus, 2005–2020, n=20, 727; SPUM-ACS, 2009–2017, n=2, 239). Sex disaggregated analyses were stratified according to the mortality endpoint of the score (in-hospital death, death at 6 months, death at 1 year), the clinical setting (calculated at admission and calculated for hospital survivors, respectively), the geographic region (United Kingdom and Switzerland, respectively) and the level of care (all hospitals and PCI-capable university hospitals, respectively). The area under the receiver operating characteristic curve (AUC), the average prediction error (APE), and the misclassification rate (MCR) were compared between women and men. Results: The discriminatory performance of GRACE 2.0 for in-hospital death was lower and the APE and MCR were higher in women as compared to men in the United Kingdom (AUC female: 80.4%, 95% confidence interval [CI], 80.0 to 80.8, AUC male: 84.7%, 95% CI, 84.4 to 85.1, p<0.001; APE female: 0.0512, 95% CI, 0.0501–0.0522, APE male: 0.0357, 95% CI, 0.0351 to 0.0363; MCR female: 5.81%, 95% CI, 5.68 to 5.94, MCR male: 3.96, 95% CI, 3.89 to 4.03) and in Switzerland (AUC female: 84.2%, 95% CI, 81.4 to 86.8, AUC male: 88.5%, 95% CI 87.1–89.7, p=0.003; APE female: 0.0420, 95% CI 0.0376 to 0.0465, APE male: 0.0312, 95% CI 0.0289 to 0.0335; MCR female: 4.98%, 95% CI 4.39 to 5.56, MCR male: 3.69%, 95% CI, 3.39 to 4.00). Similar results were obtained for 6-month death and 1-year death endpoints across clinical settings, geographic regions, and levels of care. The risk of in-hospital death relative to males was increased in females that GRACE 2.0 classified as low-to-intermediate risk (suggesting no early invasive management strategy) in the United Kingdom (relative risk [RR]: 1.61, 95% CI, 1.50 to 1.74, p<0.001) and in Switzerland (RR: 1.84, 95% CI, 1.28 to 2.64, p<0.001). Conclusion: Thus far, this is the largest investigation on the GRACE risk score. We confirmed good overall score performance and found decreased performance in contemporary female patients with NSTE-ACS irrespective of the mortality endpoint, the clinical setting, the geographic region, and the level of care. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss National Science FoundationSwiss Heart Foundation